Pediatric otorhinolaryngology surgeries for foreign bodies: A retrospective observational study in Tamale Teaching Hospital - Abdul R. Alhassan; Mahadi Iddrisu; Nurudeen Abdul‐Karim; Rhubamatu Iddrisu; Mohammed A. Baba (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objective This present study investigated the prevalence, characteristics, and management of ear, nose, and throat (ENT) foreign body (FB) in the pediatric population of Tamale. Study Design Retrospective observational study for otorhinolaryngology surgeries from 2019 to 2022 for children aged 17 years and below at Tamale Teaching Hospital. Methods A checklist created was used to collect data from the Otorhinolaryngology Surgeries records from 2019 to 2022. Chi‐square and binary logistics regression analysis were done for associations. The level of statistical significance was set at 0.05. Results Two hundred and sixty‐three cases were included in this study, and the mean age of the study participants was (4.3 ± 3.8) years with a minimum age of 1 month and a maximum age of 17 years. Most (65.4%) of the study participants were under‐5 years. The prevalence of FB in this study was 47.9%. The majority (54.8%) of the ENT FB incidence was through ingestion. Almost half (50.8%) of the ENT FB was removed through esophagoscopy. Among the foreign bodies, the coin was the most common (44.5%). Those less than 1 year were more likely to encounter FB than those 12 years and above (adust odds ratio [AOR] = 27.7, 95% confidence interval [CI] = 4.7–164.6). Again, those of 5 to less than 12 years were more likely to encounter ENT FB than those 12 years and above (AOR = 5.7, 95% CI = 1.2–26.3). Conclusions Foreign bodies are a common occurrence in pediatric otorhinolaryngology surgeries in Tamale Teaching Hospital. Younger children are more likely to report for otorhinolaryngology surgeries for FB in Tamale Teaching Hospital.